New Qinscyphus material from the Fortunian of South China - Zhang, Yanan; Liu, Yunhuan; Shao, Tiequan; Qin, Jiachen (Frontiers in Earth Science, 2023)
Microscopic medusozoans from the Cambrian Fortunian stage of South China are well known for their exceptionally preserved embryos and elongated tubes. However, additional details of their morphology remain unclear. This paper describes new medusozoan fossils showing the whole apical complement and covering the morphological integrity of Qinscyphus. The apical part of Qinscyphus is considered to be soft during early ontogeny, and the inverted pentagonal pyramid may gradually form with growth and development. This discovery of the apical complement of Qinscyphus is novel and essential to complement the external morphology of early medusozoan fossils. More importantly, the new specimens have different annuli with triangular thickenings, providing a more comprehensive view on the developmental sequence of Qinscyphus. Therefore, this work allows a better understanding of early medusozoans ecology and evolution.